IL-18 Attenuates Experimental Choroidal Neovascularization as a Potential Therapy for Wet Age-Related Macular Degeneration - Lavelle, Edward; Gardiner, Clair; Campbell, Matthew; Humphries, Peter; Fallon, Padraic; Humphries, Marian; Doyle, Sarah; Brennan, Kiva (My University, 2014)
Age-related macular degeneration (AMD) is the most common form of central retinal blindness globally. Distinct processes of the innate immune system, specifically activation of the NLRP3 inflammasome, have been shown to play a central role in the development of both "dry" and neovascular ("wet") forms of the disease. We show that the inflammatory cytokine interleukin-18 (IL-18) can regulate choroidal neovascularization formation in mice. We observed that exogenous administration of mature recombinant IL-18 has no effect on retinal pigment epithelial (RPE) cell viability, but that overexpression of pro-IL-18 or pro-IL-1β alone can cause RPE cell swelling and subsequent atrophy, a process that can be inhibited by the promotion of autophagy. A direct comparison of local and systemic administration of mature recombinant IL-18 with current anti-VEGF (vascular endothelial growth factor)-based therapeutic strategies shows that IL-18 treatment works effectively alone and more effectively in combination with anti-VEGF therapy and represents a novel therapeutic strategy for the treatment of wet AMD.
PUBLISHED
Keywords: Blindness; Ageing; Immunology, Inflammation & Infection